Determinants of perceived auditor independence for Malaysian financially distressed companies - Dharmaraj, D. Joyce Christina; Muhammad Sori, Zulkarnain; Mohd Saat, Nur Ashikin (Imperial Publishing House, 2017)
The determinants of perceived auditor independence were identified for financially distressed companies in Malaysia. These determinants included country-specific variables such as ethnicity – specifically, of the external auditor, directors, and majority shareholders - and political connection. A survey captured the perceptions of practitioners registered with the Malaysian Institute of Accountants and the data was factor analyzed. The focus on financially distressed companies and the inclusion of country-specific variables resulted in a different combination of determinants from existing auditor independence literature.